Characteristics of Post-Traumatic Stress Symptoms among Residents in Temporary Shelters Following the 2025 Uiseong Wildfire - Jin Suk Koo (Journal of Korean Medicine, 2026)
Objectives: This study aimed to assess the level of post-traumatic stress disorder (PTSD) among residents who stayed in temporary shelters following the 2025 Uiseong wildfire and to examine differences in symptom severity according to sociodemographic characteristics. The findings are intended to provide baseline data for establishing shelter-based post-disaster mental health monitoring systems and community-centered intervention strategies.Methods: A cross-sectional survey was conducted with 100 wildfire survivors using purposive and convenience sampling methods. PTSD was measured using a 20-item self-report questionnaire based on a 5-point Likert scale. Participants were classified into risk groups according to a predefined cutoff score. Data were analyzed using descriptive statistics, chi-square tests, and correlation analysis, with the level of statistical significance set at p < .05.Results: The mean PCL-5 score was 39.08 (±17.32), and 65.0% (n = 65) of participants were classified as high-risk (≥33 points). Symptom severity was highest for intrusion, followed by hyperarousal, negative alterations in cognition and mood, and avoidance. No significant association was found between total PCL-5 score and sex or age. However, women showed significantly higher scores on selected symptom items (p < .05), and age was positively correlated with an avoidance symptom item (p = .015).Conclusions: A high proportion of wildfire survivors in temporary shelters were classified as being at high risk for PTSD. Differences in symptom patterns according to sex and age suggest the need for systematic mental health screening and differentiated management strategies in post-disaster settings. These findings provide practical evidence for developing shelter-based disaster mental health monitoring systems and tailored community intervention programs.